How to encourage business professionals to adopt sustainable practices? Experimental evidence that the 'business case' discourse can backfire. (10th February 2021) - Rode, Julian; Heinz, Nicolai; Cornelissen, Gert; Le Menestrel, Marc
Abstract: Appeals to companies to adopt more sustainable practices are typically either framed as a request to assume 'responsibility' towards society and the future of the planet, or as a 'business case' (BC) for sustainability. The business case discourse emphasizes how sustainable practices can enhance (financial) business performance. We conducted a survey-based online experiment with business professionals to empirically explore the effectiveness of the two discourse types in motivating business actors to adopt more sustainable practices. Our results suggest that professionals believe that the business case discourse is more effective in encouraging businesses to engage with sustainability than the responsibility discourse. However, exposure to the business case discourse in the experiment did not lead these professionals to state a stronger motivation or intention to act in favour of sustainability within their organization. Furthermore, compared to the responsibility discourse, an appeal based on a business case discourse resulted in less approval for pro-environmental investments when these could not be justified by reputational benefits. Since effective measures to improve corporate environmental performance do not always involve win-win situations, our results raise concerns about the use of the business case approach to encourage companies to adopt sustainable practices. Highlights: Sustainability appeals to companies either request responsibility or highlight the 'business case'. An online experiment tests effects of business case (BC) vs. responsibility messaging. The BC discourse does not lead to stronger intentions to act for sustainability. The BC discourse leads to fewer sustainability investments in trade-off situations.